Natural convection and entropy generation of non-Newtonian nanofluids with different angles of external magnetic field using GPU accelerated MRT-LBM. (February 2022) - Rahman, Aimon; Redwan, Didarul A.; Thohura, Sharaban; Kamrujjaman, Md.; Molla, Md. Mamun
Abstract: In this article, the influence of applied magnetic field on the non-Newtonian power-law nanofluid in a rectangular-shaped enclosure has been studied and investigated by deploying the multiple-relaxation-time (MRT) lattice Boltzmann method (LBM). The enclosure is filled with water containing Cu nanoparticles. For the proper investigation, the equation for mass, momentum, and energy has been governed by the lattice Boltzmann method for non-Newtonian power-law nanofluid. The code validation with the previous studies is presented in the paper. The study presented here takes consideration of a wide range of magnetic field angles ( γ  = 0°, 30°, 45°, 90° and 120°), thermal Rayleigh number ( Ra  = 10 4 and 10 5 ), power-law index ( n  = 0.6, 1.0 and 1.4) of non-Newtonian power-law fluid. The study found that the average Nusselt number rises with the increment of magnetic angle up to γ  = 90°, then it starts to exacerbate when γ  = 120°. The average Nusselt number also increases for the higher values of the power-law index and maximum when n  = 1, then it starts to decrease when the fluid becomes shear-thickening. Furthermore, finally, the entropy profile of the study is thoroughly investigated in detail.